2019
DOI: 10.3390/ijms20061355
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tocotrienol in Preventing Male Osteoporosis—A Review of Current Evidence

Abstract: Male osteoporosis is a significant but undetermined healthcare problem. Men suffer from a higher mortality rate post-fracture than women and they are marginalized in osteoporosis treatment. The current prophylactic agents for osteoporosis are limited. Functional food components such as tocotrienol may be an alternative option for osteoporosis prevention in men. This paper aims to review the current evidence regarding the skeletal effects of tocotrienol in animal models of male osteoporosis and its potential an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 157 publications
(235 reference statements)
0
21
0
Order By: Relevance
“…Three groups receiving MIA injection were administrated annatto tocotrienol orally at the dose of 50, 100, 150 mg/kg/day a day after the MIA injection. The doses were based on previous studies, whereby annatto tocotrienol demonstrated skeletal effects at doses between 60–100 mg/kg [20]. The sham and MIA group were supplemented with an equal volume of olive oil.…”
Section: Methodsmentioning
confidence: 99%
“…Three groups receiving MIA injection were administrated annatto tocotrienol orally at the dose of 50, 100, 150 mg/kg/day a day after the MIA injection. The doses were based on previous studies, whereby annatto tocotrienol demonstrated skeletal effects at doses between 60–100 mg/kg [20]. The sham and MIA group were supplemented with an equal volume of olive oil.…”
Section: Methodsmentioning
confidence: 99%
“…T3 and TF exists naturally as alpha-(α-), beta-(β-), gamma-(γ-), and delta-(δ-) isomers depending on the position of the side chains on the chromanol ring. Both TF and T3 have been regarded as nutraceuticals with a wide range of biological activities against pathological complications, including dyslipidemia [6], cardiovascular [7], musculoskeletal, rheumatoid diseases [8][9][10][11][12][13], gastric [13], neurodegenerative [14], and metabolic diseases [6,15], as well as cancers [16]. The biological effects of T3 can be contributed by its potent anti-inflammatory, anti-oxidative, anti-tumor, cholesterol-lowering [through inhibition of 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR) activity] activities [8,9,17].…”
Section: Introductionmentioning
confidence: 99%
“…Palm-based tocotrienol contains approximately 75% tocotrienol and 25% tocopherol, whereas annatto-derived tocotrienol solely consists of tocotrienol (99.9%) with the absence of tocopherol [13]. The ability of tocotrienol mixture to mitigate MetS-associated medical conditions [14] and bone deterioration [15,16] has been well-established. Tocotrienol was found to alleviate MetS features through its potent anti-inflammatory [17], anti-oxidative [18,19] and cholesterol-reduction properties [20].…”
Section: Introductionmentioning
confidence: 99%